SYSTEMATIC LITERATURE REVIEW (SLR): THE INFLUENCE OF ENTREPRENEURSHIP EDUCATION AND SELF-EFFICACY ON ENTREPRENEURIAL INTENTION - Prasasti, Meliana Anggita; Ulfa Kamalia, Putri (Sekolah tinggi ilmu ekonomi pemuda, 2025)
The high unemployment rate and low level of entrepreneurship in Indonesia are the main challenges in achieving developed country status. One of the strategies that can be taken is to encourage entrepreneurial intentions, especially among the younger generation. This study aims to examine the effect of entrepreneurship education and self-efficacy on entrepreneurial intention through the Systematic Literature Review (SLR) approach. Entrepreneurship education is considered capable of fostering entrepreneurial knowledge, skills and mindset, especially if it is designed in a practical and applicable manner. Meanwhile, self-efficacy, which is an individual's belief in their ability to face challenges and take risks, plays an important role in shaping one's intention to start a business. A review of the literature shows that both factors have a positive and significant influence on entrepreneurial intentions. Hands-on education and a supportive environment can strengthen self-efficacy and prepare individuals to become resilient and independent entrepreneurs. These findings provide an important basis for the development of more effective and sustainable entrepreneurship education strategies.